Application of between- stand cooling in the production hot – rolled strips - U. Muhin; S. Belskij; E. Makarov; T. Koynov (Fracture and Structural Integrity)
Medium grain size has been uneven over the length of hot-rolled strips of austenite of low-carbon steel during rolling on continuous mill. Assess the possibilities of metal microstructure of hot-rolled strip stabilization system between-stand refrigeration line. Rolling low carbon strips developed modes with increasing temperature end rolling along the length of the strips and rolling modes using between-stand cooling with variable flow cooling water. Using this technology mode allows you to get a uniform cooling microstructure of metal strips and cut to length machine time rolling on 14 – 18%. Treatment with an increased acceleration stabilizes the metal microstructure on rolling strips on top of the thread speed and reduces the machine time rolling on 3-9%.